The Rise and Decline(?) of the Modern in Sweden - Reflected through Cultural Resource Management Archaeology - Magnusson Staaf, Björn (Current Swedish Archaeology, 2000)
A social and ideological trend that has been most influential in the 20’" century is modernism. It is of interest to closer examine the relationship between archaeology and the western social-liberal modernistic project. The archaeology related to Cultural Resource Management in Sweden is a suitable for a study of this kind. This article tries to illustrate this by presenting a case study from Malmö in Scania, south Sweden. The Swedish modern project went hand in hand with industrialization. This development has been of importance for the accumulation of archaeological data. Modernistic ideas were however also largely to influence archaeological methods and interpretations.